Correlação entre os genes p53 e HIF-1-Alfa por técnica de imuno-histoquímica para avaliar os tumores de mulheres com câncer de ovário que obtiveram resposta positiva ou negativa ao tratamento com quimioterapia - Escani, Juliana Cahale [UNIFESP] (2020)
Introduction: Ovarian cancer is considered one of the most lethal gynecological cancers for women. This cancer has four stages and can originate from different cell types. There are some factors that can lead to a higher risk of ovarian cancer such as family history, age and obesity. In contrast, there are some preventive factors for this cancer like a diet rich in healthy foods and physical activity. The absence of specific symptoms of this cancer leads to a delay in diagnosis, causing, in most cases, a late diagnosis of the cancer at a more advanced stage. Some tumor markers are related to ovarian cancer, such as p53 antibody. Objective: This study was intended to evaluate the correlation between immunohistochemical results of p53 antibody with clinical, demographic and anatomopathological data of the patients. Methods: A TMA (Tissue Microarray) was constructed with samples from 138 patients with high-grade serous epithelial ovarian cancer with stage III for analysis of the antibody. P53 antibody have been previously validated by immunohistochemistry. After validation, immunohistochemical was used to analyze the p53 protein in the TMA slide. Results: Results were statistically analyzed. The average age of patients diagnosed with ovarian cancer was 59 years. From 103 patients of the final p53 analysis, 70 patients were treatment sensitive and 26 patients were resistant. Only 10 patients had blood vascular invasion. Conclusion: The immunohistochemical results for the p53 antibody were directly related to age, sensitivity to adjuvant chemotherapy, relapse, death, mitosis in 10 fields and disease-free survival. Besides that, some clinical aspects were related to each other, such as, patients resistant to adjuvant chemotherapy presented high amount of mitoses in 10 fields.